2022
DOI: 10.3892/etm.2022.11459
|View full text |Cite
|
Sign up to set email alerts
|

Protective role of Achyranthes bidentata polysaccharides against chondrocyte extracellular matrix degeneration through lncRNA GAS5 in osteoarthritis

Abstract: Achyranthes bidentata polysaccharides (ABPS) is an active ingredient of the flowering plant Achyranthes bidentata that has been previously reported to be effective for the treatment of osteoarthritis (OA). However, the underlying molecular mechanism remain to be fully clarified. Emerging studies have shown that the long non-coding RNA (lncRNA) growth arrest-specific transcript 5 (GAS5) is involved in the pathogenesis of OA. Therefore, the present study aimed to investigate the potential mechanism of ABPS by fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…A large number of studies have found that the intervention of specific LncRNA has an inhibitory effect on the development of osteoarthritis. For example, Achyranthes bidentata polysaccharide (ABP) can slow down the degradation of ECM by regulating the expression of lncRNA GAS5 77 . It can also inhibit thapsigargin (TG)‐induced chondrocyte endoplasmic reticulum stress (ERS) 78 through the lncRNA NEAT1/miR‐377‐3p axis to protect osteoarthritis.…”
Section: Long Non‐coding Rna(lncrna)mentioning
confidence: 99%
See 1 more Smart Citation
“…A large number of studies have found that the intervention of specific LncRNA has an inhibitory effect on the development of osteoarthritis. For example, Achyranthes bidentata polysaccharide (ABP) can slow down the degradation of ECM by regulating the expression of lncRNA GAS5 77 . It can also inhibit thapsigargin (TG)‐induced chondrocyte endoplasmic reticulum stress (ERS) 78 through the lncRNA NEAT1/miR‐377‐3p axis to protect osteoarthritis.…”
Section: Long Non‐coding Rna(lncrna)mentioning
confidence: 99%
“…For example, Achyranthes bidentata polysaccharide (ABP) can slow down the degradation of ECM by regulating the expression of lncRNA GAS5. 77 It can also inhibit thapsigargin (TG)‐induced chondrocyte endoplasmic reticulum stress (ERS) 78 through the lncRNA NEAT1/miR‐377‐3p axis to protect osteoarthritis. In conclusion, lncRNA plays an important role in regulating gene expression, maintaining cartilage and synovial cell phenotype, and stabilizing the intra‐articular environment.…”
Section: Long Non‐coding Rna ( Lncrna ...mentioning
confidence: 99%
“…Achyranthes bidentata polysaccharides (ABPS) are a group of main bioactive components of Achyranthes (He et al, 2017). At the level of the microenvironment, ABPS regulates ECM homeostasis via inhibition of the lncRNA GAS5 and MMP-13 as well as the upregulation of TIMP-1 (Fu, Qiu, Huang, Mei, et al, 2022). At the level of cell phenotype and subcellular organelles, as known, studies of other NAIPs on chondrocytes have demonstrated that Wnt/β-catenin signaling pathway inhibition obviously suppresses OA inflammation (Zeng et al, 2014).…”
Section: Achyranthes Bidentata Polysaccharidesmentioning
confidence: 99%
“…In a rat model of OA, BBR T A B L E 5 Polysaccharides. Regulates ECM homeostasis (Fu, Qiu, Huang, Mei, et al, 2022) Upregulation of TIMP-1. Actives the Wnt/β-catenin signaling pathway.…”
Section: Berberinementioning
confidence: 99%
See 1 more Smart Citation